Traumatic Brain Injury in Honduras: The Use of a Paper‑based Surveillance System to Characterize Injuries Patterns - Erica Johnson; Cristina Rodriguez; Juan C. Puyana; Francisco J. Bonilla-Escobar (International Journal of Medical Students, 2022)
Background: Traumatic brain injuries (TBI) are a leading cause of death and disability worldwide. Violence is the leading cause of mortality in Honduras. However, the incidence and impact of TBI in this low-middle income country (LMIC) is unknown. The aim of this study is to describe the epidemiology of TBI in Honduras, as captured by an injury surveillance tool in the country’s major referral center.